Reading Judas : the Gospel of Judas and the shaping of Christianity - Pagels, Elaine (Allen Lane, 2007)
Lost for 1,600 years, the Gospel of Judas was discovered in Egypt in the 1970s. Nearly 30 years later, when it reached scholars who could unlock its meaning, it was clear this was a major biblical discovery. In its telling our understanding of Jesus' death, of Judas' betrayal, and of why God allowed it, are all altered.